2000
DOI: 10.1002/(sici)1097-0088(20000315)20:3<317::aid-joc476>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation fluctuations in the Nepal Himalaya and its vicinity and relationship with some large scale climatological parameters

Abstract: Precipitation records from 78 stations distributed across Nepal were analysed and all‐Nepal (1948–1994) and subregional records (1959–1994) were developed. The all‐Nepal and regional precipitation series showed significant variability on annual and decadal time scales. Distinct long‐term trends were not found in these precipitation records. The all‐Nepal record agrees well with the precipitation records from northern India, while it does not compare well with the all‐India precipitation record. The all‐Nepal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
230
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(254 citation statements)
references
References 30 publications
17
230
1
Order By: Relevance
“…Many studies have reported that there is increase in frequency of intense rainfall events, but the total annual precipitation and the number of rainy days have decreased in many parts of Asia 5,[14][15][16][17][18][19] . Increase in extreme rainfall events may have led to severe floods and landslides.…”
Section: Studies Of Extreme Rainfall Trends In Indiamentioning
confidence: 99%
“…Many studies have reported that there is increase in frequency of intense rainfall events, but the total annual precipitation and the number of rainy days have decreased in many parts of Asia 5,[14][15][16][17][18][19] . Increase in extreme rainfall events may have led to severe floods and landslides.…”
Section: Studies Of Extreme Rainfall Trends In Indiamentioning
confidence: 99%
“…Based on various local and regional analyses, it is predicted that temperatures in the HKH will continue to rise in the future. For example, Rupa et al (2006) predict that temperatures on the Indian subcontinent will rise between 3.5 and 5.5 o C by 2100, while, Shi (2001) The historical trends in precipitation in HKH region are less clear, with varied and inconsistent results in different areas (Bhutiyani et al, 2010;Shrestha et al, 2000;Xu B et al, 2009). Ice core studies on the Tibetan Plateau indicate that both wet and dry periods have occurred since 960 AD (Tan et al, 2007) and 1600 AD (Yao et al, 2008).…”
Section: Climate Changementioning
confidence: 99%
“…It is important to note that substantial interdecadal variability exists in both the Indian and the east Asian monsoons. [WGI 3.3 Generally, the frequency of occurrence of more intense rainfall events in many parts of Asia has increased, causing severe floods, landslides, and debris and mud flows, while the number of rainy days and total annual amount of precipitation have decreased (Zhai et al, 1999;Khan et al, 2000;Shrestha et al, 2000;Izrael and Anokhin, 2001;Mirza, 2002;Kajiwara et al, 2003;Lal, 2003;Min et al, 2003;Ruosteenoja et al, 2003;Zhai and Pan, 2003;Gruza and Rankova, 2004;Zhai, 2004). However, there are reports that the frequency of extreme rainfall in some countries has exhibited a decreasing tendency (Manton et al, 2001;Kanai et al, 2004).…”
Section: 221mentioning
confidence: 99%